Elie Dimitras, Εισαγωγή εις την κοινωνιολογίαν της αναπτύξεως (Eisagogi eis tin koinvniologian tis anaptyxeos)(Introduction to the sociology of development) - Kourvetraris, George A. (The Greek Review of Social Research, 1974)
[Δε διατίθεται περίληψη / no abstract available]